PENGARUH TEGANGAN AIR PORI NEGATIF TERHADAP KUAT GESER TANAH LEMPUNG - Robby Nikolus (Jurnal Teknologi Berkelanjutan, 2012)
Soil in the sampling area undergoes drying-wetting cycle in therainy season and the dry season. This could make pore water in the soilto fluctuate so that the suction changes. The experiment used no.42 Whatman paper filter to measure suction and direct shear test to measure the shear strength.No. 42 Whatman paper filter was placed in the sample inside a pvc tube. It took three variatons of water content. The first variation was wetting variation. Sample was given water so that the water content increase to 25%, 30% and 35%. The second variation was drying variation. Sample was stored in a desicator filled silica gel, so that water content decreased to 15%, 10%, 5% and 0%. The third variation was wetting-drying variation. Sample at maximum water content (35%) was dried gradually so that water content decreased to 30%, 25%, 15%, 10%, 5% and 0%. This experiment indicates that increasing and decreasing suction results in the variation of the shear strength and the volume soil. Variation in the soil volume is the alteration of void ratio (e), degree of saturation (Sr) and water content (w). The result during the wetting procces or rainy season, the soil shear strength will decrease along with decreasing suction. In drying procces or dry season, the soil shear strength will increase along with increasing suction.